The Role of Infant Gut Microbiota Modulation by Perinatal Maternal Probiotic Intervention in Atopic Eczema Risk Reduction - Puisto, Reetta; Gómez-Gallego, Carlos; Collado, Maria Carmen; Turta, Olli; Isolauri, Erika; Rautava, Samuli (KARGER, 2025)
Introduction: Probiotics have shown potential in reducing the occurrence of atopic eczema in high-risk infants. We aimed here to assess whether the preventive effect of maternal probiotic administration stems from compositional changes in early gut microbiota.
Methods: This study included 46 mother-infant pairs from an original randomized controlled trial assessing the impact of maternal probiotic intervention with either the combinations of Lacticaseibacillus rhamnosus LPR and Bifidobacterium longum BL999, or Lacticaseibacillus paracasei ST11 and Bifidobacterium longum BL999, or placebo beginning 2 months before expected delivery and ending 2 months after birth. All children were vaginally delivered, full term and breastfed. During the 2-year follow-up period, the children were clinically evaluated by physicians for atopic eczema, and their gut microbiota was profiled at 1 and 6 months of age by 16S rRNA gene sequencing using an Illumina sequencing platform.
Results: Altogether, 19 of 46 children developed atopic eczema by the age of 2 years. At 1 and 6 months of age, gut microbial diversity was similar between children who developed atopic eczema and their healthy controls, but at the age of 6 months, children who developed atopic eczema manifested with significantly higher relative abundance of Clostridia. Probiotic intervention did not significantly influence microbial diversity, and the effects on microbial composition were not consistent with the changes associated with the development of atopic eczema.
Conclusion: The reduction of the risk of atopic eczema achieved by perinatal maternal probiotic intervention does not seem to require substantial gut microbiota modulation.